Implementasi Good Corporate Governance dalam Pengelolaan Dana BOS di SMP Negeri 18 Purworejo - Kamaliah Kamaliah; Rusmiyatun Rusmiyatun; Wiyonoroto Wiyonoroto (STIE Rajawali Purworejo, 2026)
This study aims to determine how the implementation of Good Corporate Governance (GCG) is carried out in the management of School Operational Assistance (BOS) funds at SMP Negeri 18Purworejo. The variables used in this research are transparency and accountability. This research was conducted during the 2024 implementation of GCG in BOS fund management. The research method applied was qualitative, with data collected through observation, interviews, and documentation study. The respondents in this study consisted of the Principal, the BOS Treasurer, representatives of the School Committee, teachers, and parents. The findings reveal that the implementation of Good Corporate Governance (GCG), particularly the principles of transparency and accountability in BOS fund management at SMP Negeri 18 Purworejo, has been carried out effectively. BOS funds are managed openly by involving stakeholders from the planning stage to the utilization and accountability process. The management of BOS funds is implemented in accordance with the technical guidelines outlined in the Regulation of the Minister of Education, Culture, Research, and Technology Number 63 of 2023. This indicates that the school has managed the funds in a transparent and accountable manner. It is suggested that school should also publish BOS fund utilization information on the school`s official website to ensure broader public access.